Uzaktan Yönetim: Yeni Bir Yönetim Yaklaşımı(Remote Management: A New Management Approach) - Ferit ÖLÇER (Yönetim ve Ekonomi, 2004)
For some managers, managing virtual workforce requires a new management approach, while for other managers, it is a natural extension of their existing effective management techniques. But, remote management requires learning new skills and adjusting management style. So, many managers may need to modify the way they supervise remote workers. The successful management of virtual workforce is primarily dependent upon effective communications and trust, which requires managing by results, not by sight. Also, managers should use new ways for performance apprasing and compensating virtual workforce. In this study, remote management techniques are discussed and methods that are used for performance appraisal and compensation of virtual workforce are examined.